Penerapan Asas Restitusi Sebagai Pedoman Kepastian Hukum Dalam Menyelesaikan Perkara Korban Perdagangan Orang Berdasarkan Undang-Undang Nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang (Studi Kasus Perkara Berdasarkan Nomor 187/Pid.Sus/2018/PN.Grt) - Kartika, Ratna (Jurnal Hukum Media Justitia Nusantara, 2022)
The purpose of this research was to find out how the legal certainty the restitution of victims for criminal acts of trafficking in Indonesia and how the application of restitution in judicial practice. By using the normative legal research method, it is concluded that: 1. The law has guaranteed legal certainty in the provision of restitution rights for victims of TPPO through the authority of law enforcement officials starting from the stages of investigation, prosecution and judges' decisions. Legal Certainty of Restitution for Victims of Crime in Trafficking in Persons in Indonesia is still dependent on the Court. Practically, what happens in the jurisdiction of the Decision of the Garut District Court Number 187/Pid.Sus/2018/PN.Grt, there is no right of restitution including in the ruling that has permanent legal force on the case of the Criminal Eradication of Trafficking in Persons. 2. Restitution of victims for trafficking in persons according to Law Number 21 of 2007 concerning Eradication of Crime in Trafficking in Persons, is compensation for victims/heirs charged to perpetrators of crimes based on court decisions that has permanent legal force for material losses and / or immateriality suffered by the victim or his heirs. Restitution as refer to the form of compensation for: loss of wealth or income; suffering; fees for medical and / or psychological care measures; and / or other losses suffered by victims as a result of trafficking in persons. Provision of restitution carrying since the decision of the first court was dropped. Restitution is carrying within 14 (fourteen) days. Tujuan dilakukannya penelitian ini adalah untuk mengetahui bagaimana kepastian hukum restitusi korban tindak pidana perdagangan orang di Indonesia dan Bagaimana penerapan restitusi dalam praktik peradilan. Dengan menggunakan metode penelitian hukum normatif disimpulkan bahwa: 1. Undang-undang telah menjamin adanya kepastian hukum terhadap pemberian hak restitusi bagi korban TPPO melalui kewenangan aparat penegak hukum mulai dari tahap penyidikan, penuntutan dan putusan hakim. Kepastian Hukum Restitusi Korban Tindak Pidana Perdagangan Orang di Indonesia masih tergantung kepada Pengadilan. Pada praktiknya yang terjadi di wilayah hukum Putusan Pengadilan Negeri Garut Nomor 187/Pid.Sus/2018/PN.Grt, tidak ada hak restitusi dicantumkan dalam amar putusan yang berkekuatan hukum tetap terhadap perkara Tindak Pidana Pemberantasan Perdagangan Orang. 2. Restitusi terhadap korban tindak pidana perdagangan orang menurut Undang-Undang Nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang, merupakan pemberian ganti rugi kepada korban/ahli waris yang dibebankan kepada pelaku tindak pidana berdasarkan putusan pengadilan yang berkekuatan hukum tetap atas kerugian materiil dan/atau immateriil yang diderita korban atau ahli warisnya. Restitusi sebagaimana dimaksud berupa ganti kerugian atas: kehilangan kekayaan atau penghasilan; penderitaan; biaya untuk tindakan perawatan medis dan/atau psikologis; dan/atau kerugian lain yang diderita korban sebagai akibat perdagangan orang. Pemberian restitusi dilaksanakan sejak dijatuhkan putusan pengadilan tingkat pertama. Pemberian restitusi dilakukan dalam 14 (empat belas) hari.